Bacterial extrachromosomal elements: role in chemical detoxification and potential cancer therapy - Chakrabarty, Ananda (Henry Stewart Talks, 2008)
Examples of degradative plasmids, Xylene and toluene degradation by TOL plasmids, The chloro-catechol orthocleavage pathway, Catabolic pathways/genes in 2,4-D degradation, Chemostatic evolution of 2,4,5-T degradative genes, Unusual genomic structure of the 2,4,5-T genes, Sequence characteristics of the clc element, Evolution of s-triazine degradative plasmids, Azurin interaction with different targets, Structural features of azurin and immunoglobulins, Secretion of azurin upon exposure to cancer cells, Sequences in released extrachromosomal DNA, Released CpG-rich DNA has anti-tumor activity
Archived at 2021/02/25